2019
DOI: 10.1371/journal.ppat.1007900
|View full text |Cite
|
Sign up to set email alerts
|

Perturbations of the ZED1 pseudokinase activate plant immunity

Abstract: The Pseudomonas syringae acetyltransferase HopZ1a is delivered into host cells by the type III secretion system to promote bacterial growth. However, in the model plant host Arabidopsis thaliana , HopZ1a activity results in an effector-triggered immune response (ETI) that limits bacterial proliferation. HopZ1a-triggered immunity requires the nucleotide-binding, leucine-rich repeat domain (NLR) protein, ZAR1, and the pseudokinase, ZED1. Here we demonstrate that HopZ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 92 publications
(186 reference statements)
0
52
0
Order By: Relevance
“…Although the lack of autoactive mutations for ZAR1 does not allow us to specifically analyze the intramolecular interactions present in active complexes, we demonstrated that associations between the domains must have some flexibility to allow for conformational changes upon activation. Since our interaction assays were carried out in vivo, we also cannot exclude the possibility that other host proteins help to mediate the associations (Bastedo et al, 2019). Our data show that ZAR1 is modulated by subtle conformational changes that are finely controlled, and that ZAR1 displays specificity in its intramolecular interactions despite broad structural similarity with other NLRs.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Although the lack of autoactive mutations for ZAR1 does not allow us to specifically analyze the intramolecular interactions present in active complexes, we demonstrated that associations between the domains must have some flexibility to allow for conformational changes upon activation. Since our interaction assays were carried out in vivo, we also cannot exclude the possibility that other host proteins help to mediate the associations (Bastedo et al, 2019). Our data show that ZAR1 is modulated by subtle conformational changes that are finely controlled, and that ZAR1 displays specificity in its intramolecular interactions despite broad structural similarity with other NLRs.…”
Section: Discussionmentioning
confidence: 92%
“…HopZ1a triggers a strong HR that depends on the RLCK ZED1 (HOPZ-EFFECTOR-TRIGGERED IMMUNITY DEFICIENT 1) and ZAR1 (Lewis et al, 2008(Lewis et al, , 2010(Lewis et al, , 2013Baudin et al, 2017). HopZ1a acetylates ZED1, which is hypothesized to trigger ZAR1 activation, likely through conformational changes (Lewis et al, 2013;Baudin et al, 2017;Bastedo et al, 2019;Wang et al, 2019b). The recognition of AvrAC and HopF2a is more complex and involves other proteins that mediate a connection between the effector and the ZAR1-RLCK complex (Wang et al, 2015b;Seto et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…HopZ1a can acetylate members of a family of PBLs (receptor‐like cytoplasmic kinases) and promote their interaction with ZED1 and ZAR1 to form a ZAR1‐ZED1‐PBL ternary complex. Interactions between ZED1 and PBL kinases are determined by the pseudokinase features of ZED1, and mutants designed to restore ZED1 kinase motifs can bind to PBLs, recruit ZAR1, and trigger ZAR1‐dependent immunity in planta (Bastedo et al , 2019). TaCRK2 may have kinase activity.…”
Section: Discussionmentioning
confidence: 99%
“…SZE1 and SZE2 directly interact with HopZ1a and are proposed to help mediate conformational changes that lead to ZAR1 activation (Liu et al, 2019). In addition, several PBS1‐like kinases (PBLs) have also been shown to be targeted by HopZ1a and participate in ZAR1‐mediated recognition (Bastedo et al, 2019). It would, therefore, be interesting to broaden our diversity screen to these other players in HopZ1a‐induced immunity and investigate how evolution shaped these proteins in relation to ZED1 and ZAR1.…”
Section: Discussionmentioning
confidence: 99%